Resztki awangardy. Powojenne pisma filmowe Tadeusza Peipera - Wójtowicz, Aleksander (Zagadnienia Rodzajów Literackich, 2019)
Postwar film writings of Tadeusz Peiper are the protest against “the policics of the voice” (M. Dolar) of the Polish social realist and propaganda films. Escaping from be-ing involved in communist ideology, the author creates a cinematic theory concentrated on nonverbal elements. An important role is played by categories extremely far from the constructivist discourse of art (nostalgia, community, non-human).